Promises to keep : how Jackie Robinson changed America - Robinson, Sharon, 1950- (New York : Scholastic Press, 2004)
A biography of baseball legend Jackie Robinson, the first African American to play in the major leagues, as told by his daughter.
Includes index.
English language and literature.
Keywords: Robinson, Jackie, -- 1919-1972 -- Juvenile literature; Robinson, Jackie, -- 1919-1972.; African American baseball players -- Biography -- Juvenile literature; African Americans -- Biography -- Juvenile literature; Baseball players -- Biography -- Juvenile literature; Conduct of life -- Juvenile literature; Baseball players; African Americans -- Biography; Race relations; United States -- Race relations -- Juvenile literature